Pengembangan E-Komik Matematika Berbasis STEM untuk Meningkatkan Kemampuan Berpikir Kreatif Matematis Siswa Pada Materi Bangun Ruang Sisi Datar Kelas VIII SMP. - Novita, Amalia; Huda, Nizlel; Junita, Ranisa (Jurnal PEKA (Pendidikan Matematika), 2025)
This research aims to describe the development process and quality of STEM-based mathematics e-comics designed to enhance students’ creative thinking skills in flat-sided geometric materials for eighth-grade students at SMP. The study follows a Research and Development (R&D) approach using the ADDIE development model. The test subjects included a team of experts, a mathematics teacher, and eighth-grade students at SMPN 56 Merangin. The findings indicated a high level of validity, with the e-comics receiving a validity rating of 100% in terms of media and 95,24% in terms of material. The practicality rating from teachers was 100%, and it was classified as very practical. The overall practicality of the e-comics also fell under the “very practical” criteria. The effectiveness of the e-comics, as determined by an effectiveness questionnaire, scored 81,91%, which was considered “very effective.” Furthermore, a test yielded an N-Gain score of 0,65 categorizing the e-comics as quite effective. Based on the N-Gain score, it can be concluded that STEM-based mathematics e-comics effectively improve students’ creative mathematical thinking abilities.